Venturi Philosophically Revisited (Robert Venturi and the revival of modernism) - Salihu, Astrit (Identities: Journal for Politics, Gender and Culture, 2023)
This article explores the significant implications of Robert Venturi’s “Complexity and Contradiction in Architecture” on architectural discourse. By delving into Venturi’s theoretical foundation, we gain an understanding of the evolution of discursive paradigms that have shaped architectural projects in recent years. The distinction between modern and postmodern architecture primarily hinges on the argument for the necessity of architectural inclusivity advocated by Venturi. This revision challenges the entire paradigm of modern architectural exclusivity. Venturi’s concept of complexity holds a crucial place in postmodern philosophical discourse, as exemplified by Lyotard. The incommensurability of language games, which Lyotard considers as an argument for the impossibility of reducing them to a single universal judgment, parallels the incommensurability of architectural elements. Venturi emphasizes that architectural elements should not be excluded from a universal architectural premise. This complexity introduces a nuanced situation, necessitating, according to Lyotard, a new kind of sensibility to appreciate their incommensurability. Meanwhile, in Venturi’s perspective, this situation reflects the complexity that must be realized in achieving a delicate balance between inclusion and the potential avoidance of an abusive unity of exclusion. The schemata used by Lyotard to describe the transformation and liberation of various linguistic contents are generally applicable in Venturi’s context, offering insights into the liberation of architectural content. Author(s): Astrit Salihu Title (English): Venturi Philosophically Revisited (Robert Venturi and the revival of modernism) Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 104-115 Page Count: 12 Citation (English): Astrit Salihu, "Venturi Philosophically Revisited (Robert Venturi and the revival of modernism),” Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023): 104-115.